Characteristics of Lung Cancer Patients in Haji Adam Malik General Hospital Medan in 2016-2018 - Sivabalan Logawathi, Satthiyabalan; Causa Trisna Mariedina (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Lung cancer is a malignant disease in the lung where abnormalities caused by collection of genetic changes in the epithelial cells of the airway, which lead to cell proliferation that cannot be controlled. This study was conducted to determine the characteristics of lung cancer patients in Haji Adam Malik General Hospital Medan in 2016-2018. This research is a descriptive study with a case series approach. The study population was 311 lung cancer patients using Total Sampling method. The tendency of inpatient lung cancer patients visiting H. Adam Malik General Hospital Medan in 2016-2018 has decreased. The highest proportion of patients with lung cancer based on sociodemography obtained 65-69 years old age group, men with 3: 1 sex ratio, work of farmers, living outside the city of Medan, the main complaint was more than one complaint, had a history of smoking, no pleural effusion occurred, the type of adenocarcinoma histology and the method of taking a cytological fluid specimen. There was a statistically significant relationship between age with sex, sex with occupation, sex with smoking history, occupation with primary complaints, occupation with smoking history, and histology type by specimen collection and there rest have no statistically significant difference.